GOTO065054+593624: An 8.5 mag amplitude dwarf nova identified in real time via Kilonova Seekers - Killestein, T. L.; Ramsay, G.; Kennedy, M.; Kelsey, L.; Steeghs, D.; Littlefair, S.; Godson, B.; Lyman, J.; Pursiainen, M.; Warwick, B.; Krawczyk, C.; Nuttall, L. K.; et al. (EDP Sciences, 2025)
Dwarf novae are astrophysical laboratories for probing the nature of accretion, binary mass transfer, and binary evolution, but their diverse observational characteristics continue to challenge our theoretical understanding. We here present the discovery of and subsequent observing campaign on GOTO065054+593624 (hereafter GOTO0650), a dwarf nova of the WZ Sge type that was discovered in real-time by citizen scientists via the Kilonova Seekers citizen science project. The nova has an outburst amplitude of 8.5 mag. An extensive dataset charts the photometric and spectroscopic evolution of this object, and it covers the 2024 superoutburst. GOTO0650 shows an absence of visible emission lines during the high state, strong H and barely detected He II emission, and high-amplitude echo outbursts on a rapidly decreasing timescale. The comprehensive dataset we present marks GOTO0650 as a candidate period bouncer, and it highlights the important contribution made by citizen scientists to the study of Galactic transients.